Regional Variation in Rates of IVF Treatment across Australia: A Population-based Study - Louise Rawlings; Pauline Ding; Stephen J. Robson (Journal of Health Economics and Outcomes Research, 2017)
# Background There is variation in uptake of in vitro fertilisation (IVF) between countries, and Australia has high incidence rates of IVF due to universal public funding. However, it remains unclear whether there is regional variation and, if present, what might cause this.